2017
DOI: 10.1111/jfpp.13358
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged preservation of corn oil via gold nanoparticles

Abstract: Gold nanoparticles (AuNPs) as preservatives add with variable concentrations to corn oil to may improve the shelf life. AuNPs was prepared by pyrolysis in oleic acid then sample was characterized by transmission electron microscope and UV spectroscopy. Rancidity analyses and microbiological properties were performed through storage periods. The results showed that AuNPs decreases total bacterial count and chemical analyses except iodine value but shelf life increases compared to control sample. Practical appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…From data in Table (2) acid value in vegetable oils: namely Virgin olive, corn, sunflower and sesame oils reported 0.989, 0.136, 0.198 and 0.921 mg/g, respectively, these results agreed with (Squires, 1991 andAl-Sherbini et al, 2018) who reported the acid value of corn oil ranged from 0.1-1.1 mg/g (Rey, et al, 2001;Cao, et al, 2015 andGrossi, et al, 2014) who reported the acid value ranged from 0.8-2%. It was decided that the acidity of olive oil should be according to decide by the International Olive Council (IOC) in 2015 that the acidity be as follows: extra-virgin olive oil (0.8%), virgin olive oil (2%), and ordinary olive oil (3.3%).…”
Section: Acid Value and Tba Of Virgin Olive Corn Sunflower And Sesame Oilssupporting
confidence: 72%
“…From data in Table (2) acid value in vegetable oils: namely Virgin olive, corn, sunflower and sesame oils reported 0.989, 0.136, 0.198 and 0.921 mg/g, respectively, these results agreed with (Squires, 1991 andAl-Sherbini et al, 2018) who reported the acid value of corn oil ranged from 0.1-1.1 mg/g (Rey, et al, 2001;Cao, et al, 2015 andGrossi, et al, 2014) who reported the acid value ranged from 0.8-2%. It was decided that the acidity of olive oil should be according to decide by the International Olive Council (IOC) in 2015 that the acidity be as follows: extra-virgin olive oil (0.8%), virgin olive oil (2%), and ordinary olive oil (3.3%).…”
Section: Acid Value and Tba Of Virgin Olive Corn Sunflower And Sesame Oilssupporting
confidence: 72%
“…About 10 ml of 5 × 10-3 mol / dm3 of HAuCl4 added drop by drop to 100 ml of oleic acid at 200 °C. Heating was continued for an additional 5 minutes after which, the solution removed from the heater and stirred for 15 minutes until, the color turned into orange-brown ("as discussed elsewhere [15][16][17]"and modified by Al-Sherbini et al [18].…”
Section: Preparation Of Aunpsmentioning
confidence: 99%
“…The 2 nd subgroup (G3) and the 4 th subgroups (G5) were treated with 10% omega-3 oils (FLO or FIO). The 3 rd (G4) and the 5 th (G6) subgroups were fortified with 10% omega-3 oils (FLO or FIO) mixed with 17 ppm AuNPs [18]. The animals were sacrificed and blood samples were collected after eight weeks.…”
Section: Experimental Designmentioning
confidence: 99%
“…AuNPs were prepared by oleic acid pyrolysis method according to [16][17][18] and modified by Al-Sherbini et al [19]. Animals Sixty healthy adult male albino rats, weighing about 130 ± 10 g were used in the current experiment.…”
Section: Preparation Of Aunpsmentioning
confidence: 99%
“…The third subgroup (G4) and the fifth subgroup (G6) were fed on HFD (50%) +FLO/FIO (10%) mixed with 17 ppm AuNPs according to Al-Sherbini et al [19].…”
Section: Experimental Designmentioning
confidence: 99%